The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/jns.2020.53
|View full text |Cite
|
Sign up to set email alerts
|

Perceived role of hot food in the pathogenesis of oesophageal cancer: a qualitative study in the Arsi Zone, Oromia, Central Ethiopia

Abstract: Observational studies in Ethiopia have identified a positive association between hot wheat porridge consumption and oesophageal carcinoma. However, a single dietary intake cannot be a sufficient predictor of cancer among populations that have diverse dietary practices. The present study was carried out to explore the community's perspectives on the role of hot foods in the pathogenesis of oesophageal cancer in Ethiopia. Focus group discussions were conducted from May to August 2019 among purposefully selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…However, in further analysis, only wheat porridge had a signi cant positive association with the consumption of porridge at a probably carcinogenic temperature compared to maize porridge. The nding supports a qualitative study in the area that demonstrated the perceived heat retention ability of wheat porridge compared to porridge cooked from barley and maize [20]. The probable explanation could be porridges cooked from different grains may display disparities in the convective and/or evaporative heat loss mechanisms.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…However, in further analysis, only wheat porridge had a signi cant positive association with the consumption of porridge at a probably carcinogenic temperature compared to maize porridge. The nding supports a qualitative study in the area that demonstrated the perceived heat retention ability of wheat porridge compared to porridge cooked from barley and maize [20]. The probable explanation could be porridges cooked from different grains may display disparities in the convective and/or evaporative heat loss mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…The practice of consuming porridge at a carcinogenic temperature was higher than the proportion of households who consumed very hot foods in Iran [7] but lower than the study result in Kenya [16]. On the other hand, the nding supports a qualitative study that reported preferences for very hot porridge by the majority of households living in the study areas [20].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations